2018
DOI: 10.1186/s12858-018-0092-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of association of human mitochondrial lysyl-tRNA synthetase with HIV-1 Pol and tRNA3Lys

Abstract: BackgroundAn important step in human immunodeficiency virus type 1 (HIV-1) replication is the packaging of tRNA3Lys from the host cell, which plays the role of primer RNA in the process of initiation of reverse transcription. The viral GagPol polyprotein precursor, and the human mitochondrial lysyl-tRNA synthetase (mLysRS) from the host cell, have been proposed to be involved in the packaging process. More specifically, the catalytic domain of mLysRS is supposed to interact with the transframe (TF or p6*) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Recently, the molecular details of the interaction between mLysRS and Gag-Pol have been revealed (Phongsavanh et al, 2020). The C-terminal integrase subunit of Gag-Pol is shown to stabilize the tRNA Lys,3 :mLysRS interaction (Khoder-Agha et al, 2018;Phongsavanh et al, 2020).…”
Section: Trna Prime Reverse Transcription Of Retroviruses and Retrotrmentioning
confidence: 99%
“…Recently, the molecular details of the interaction between mLysRS and Gag-Pol have been revealed (Phongsavanh et al, 2020). The C-terminal integrase subunit of Gag-Pol is shown to stabilize the tRNA Lys,3 :mLysRS interaction (Khoder-Agha et al, 2018;Phongsavanh et al, 2020).…”
Section: Trna Prime Reverse Transcription Of Retroviruses and Retrotrmentioning
confidence: 99%
“…These three constructs contain the CCD dimerization domain of IN. The apparent dissociation constants of the complexes formed between these three integrase species and mLysRS were determined using a homogeneous time-resolved fluorescence (HTRF) assay described in Khoder-Agha et al [ 12 ]. Whereas the binding affinity determined for IN-∆N-H 6 ( K d of 3.0 ± 0.4 nM) was similar to that determined for native integrase (IN-H 6 ; K d of 2.6 ± 0.3 nM), no interaction could be detected with CCD-H 6 ( K d > 400 nM) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The packaging of tRNA 3 Lys from the host cell within newly made HIV-1 particles involves the formation of a ternary complex comprising the GagPol viral polyprotein, mitochondrial lysyl-tRNA synthetase and tRNA Lys from the host cell. The integrase domain located at the very C-terminus of the GagPol precursor protein (Figure 1) is the main contributor to the stability of the complex between mLysRS and GagPol [12]. The cryo-EM structural analysis of the HIV-1 STC intasome revealed that integrase is made of three well-defined structural domains (Figure 1).…”
Section: The C-terminal Domain Is the Major Region Of Integrase Interacting With Mlysrsmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 , 28 , 29 In the virus, LysRS has been proposed to interact with Gag and Gag-Pol. 30 36 Specifically, LysRS has been suggested to interact with the connection and RNase H regions in the RT domain of the Gag-Pol polyprotein. 32 However, whether LysRS affects RT maturation is unknown.…”
Section: Introductionmentioning
confidence: 99%